2022
DOI: 10.1155/2022/7359081
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Coriandrum sativum (Linn.) and Petroselinum crispum (Mill.) in Enhancing Iron Absorption: An In Silico and In Vitro Approach

Abstract: Coriandrum sativum (Linn.) and Petroselinum crispum (Mill.) are the common herbs used for culinary purposes in daily life. The chlorophyll pigment in plants is being identified with various medicinal values, whereas iron is an essential micronutrient for the proper metabolism of the human body. The current research has been aimed at predicting the role of C. sativum and P. crispum in enhancing iron absorption via an in vitro approach. C. sativum and P. crispum have been analyzed for their capability of being a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…No cytotoxicity was detected in ethanol, methanol, and aqueous extract [101]. It was determined that the carbinol extract of P. crispum seeds at different concentrations (62.5-1000 μl) did not show toxicity in Caco-2 cells by MTT assay [64].…”
Section: Toxicitymentioning
confidence: 95%
See 1 more Smart Citation
“…No cytotoxicity was detected in ethanol, methanol, and aqueous extract [101]. It was determined that the carbinol extract of P. crispum seeds at different concentrations (62.5-1000 μl) did not show toxicity in Caco-2 cells by MTT assay [64].…”
Section: Toxicitymentioning
confidence: 95%
“…The extract enabled 8.24% of the iron applied to Caco-2 cells to be absorbed by the cells and showed lower permeability (2.01×10 7 cm/s). It was concluded that parsley is a good of chlorophyll and iron and increases the absorption of iron from human intestinal cells [64].…”
Section: Activity On the Gastrointestinal Systemmentioning
confidence: 99%